Design of Composite Disc Spring for Automotive Suspension with using Numerical Simulation - Mrazek, Martin; Skovajsa, Michal; Sedlacek, Frantisek (Manufacturing Technology Journal, 2022)
This paper investigates the replacement of a conventional steel coil spring with a composite disc spring with the aim of minimizing its weight. Simulation in the CAD system Siemens NX 12 was used to determine the composite disc spring's behavior. The regression functions were stated based on the numerical simulation. Based on the regression functions the solution with the minimum weight was found using software programmed in Matlab. The prototype discs were manufactured from carbon fibre prepreg. Their load-deflection characteristics were tested and compared with the designed values. The experimental results show that using this solution reduces the weight by about 30% in this case.
Keywords: carbon fibre; composite material; disc spring; optimization